The generation of antigen-specific, major histocompatibility complex- restricted cytotoxic T lymphocytes of the CD4+ phenotype. Enhancement by the cutaneous administration of interleukin 2 (The Rockefeller University Press, 1989)
We have examined an in vitro system in which PBMC from purified protein derivative (PPD)-sensitized patients generate CTL after in vitro activation with antigen. These cells selectively destroy mycobacterial antigen PPD-pulsed monocyte targets. These CTL are of the CD4+ phenotype and exhibit MHC class II restriction. After exposure to antigen these cells require 5-7 d for maximal development, whereas, a separate antigen-independent population is generated within 3-4 d. CD8+ cells are poorly, if not at all, cytotoxic under similar conditions. Cells with properties of the NK and LAK lineage are also present in these cultures and kill other specific targets. Human rIL-2 was injected into the skin of lepromatous patients at 10-micrograms doses, given at 48-h intervals, for three doses. Peripheral blood cells obtained 8-14 d after the initiation of IL-2 injection demonstrated enhanced antigen-dependent destruction of monocyte targets. The efficacy of antigen-dependent and -independent populations and their amplification by IL-2-dependent mechanisms is discussed in terms of the local destruction of parasitized macrophages and the subsequent disposal of M. leprae.